Increasing transmission control protocol speed by reducing the acknowledgement collision probability - Suherman Suherman; Ali Hanafiah Rambe; Norshakila Haris; Anhar Anhar (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Transmission control protocol (TCP) employs acknowledgement (TCP-ACK) for every transmitted packets to ensure reliable transmission. As a result, it sends the next window packets after receiving the TCP-ACK packet of previous window. This means that the earlier the TCP-ACK packet arrives, the faster the TCP next window transmission and the better the TCP performances. To do so, there should be a special treatment to the transmitted TCP-ACK to fasten next window transmission. This paper proposes a collision probability reduction for the transmitted TCP-ACK packets so that the overall TCP delay reduces. Collision probability reduction can be implemented in many ways. Initially, mathematical analysis is provided to prove that method can work as expected. The mathematic analysis shows that when TCP-ACK collision probability is reduced, the overall TCP delay is also reduced. The proposed method is then implemented in 802.11, 802.16 and complex networks. The NS-2 simulations evaluations for the aforementioned networks and the proposed method proved that collision reductions on TCP-ACK exert average TCP delay reductions about 11.86%, 28.04% and 9.46% subsequently.The proposed method is also applicable for other TCP types.